2022
DOI: 10.1186/s12886-022-02435-6
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric traumatic cataracts in Southwest China: epidemiological profile

Abstract: Background Paediatric traumatic cataracts are an important but preventable cause of acquired blindness. Understanding the epidemiology of paediatric traumatic cataracts is a prerequisite for prevention. This study aimed to characterize the epidemiological profile of paediatric traumatic cataracts in southwest China. Methods The medical records of children (age range, 0–14 years old) who developed traumatic cataracts following open-globe injuries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies from Nigeria also reported closed globe injuries to be more associated with childhood traumatic cataract. On the contrary, open globe injuries were reported to be more associated with paediatric traumatic cataract in studies from Egypt, 4 China, 5,15 India, 8 Turkey 16 and Malaysia. 17 This disparity may be a re ection of the variation in the common agents of injury which the children are exposed to in different geographical regions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies from Nigeria also reported closed globe injuries to be more associated with childhood traumatic cataract. On the contrary, open globe injuries were reported to be more associated with paediatric traumatic cataract in studies from Egypt, 4 China, 5,15 India, 8 Turkey 16 and Malaysia. 17 This disparity may be a re ection of the variation in the common agents of injury which the children are exposed to in different geographical regions.…”
Section: Discussionmentioning
confidence: 93%
“…A preponderance of traumatic cataract among boys observed in this study is consistent with the literature that boys are more likely to have ocular injuries. [4][5][6][7][8][9][10][11][12][13][14][15][16] The unanimity in the literature may not be unconnected with the fact that boys are more likely to engage in daring activities and rough play which may predispose them to eye injury. Over 80% of the children with traumatic cataract were between the ages of 5 years and 14 years (mean of 9.1 years).…”
Section: Discussionmentioning
confidence: 99%